Analysis of Factors Affecting the Position of Indonesia's Foreign Exchange Reserves with ECM Model - Pardomuan Robinson Sihombing; Luh Putu Widya Adnyani; Marta Sundari; Miftahul Huda; Syamsul Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Teknologi dan Bisnis Ahmad Dahlan Lamongan, 2025)
A Foreign exchange reserves are a vital instrument in maintaining Indonesia's macroeconomic stability, particularly in mitigating external turmoil and stabilizing the rupiah exchange rate. This study aims to analyze the factors that affect Indonesia's foreign exchange reserves position for the period from January 2022 to August 2025 using the Error Correction Model (ECM) method. Independent variables used include the Consumer Price Index (CPI), the rupiah exchange rate against the US dollar (IDR/), and the policy rate (BI Rate). Data was obtained from the publication of Indonesian Economic and Financial Statistics (SEKI) of Bank Indonesia. The results of the Dickey-Fuller Augmented Stationarity test showed that all variables were stationary at the first difference, while the Engle-Granger co-integration test confirmed the existence of a long-term relationship between the variables. The results of the estimation indicate that, in the long term, no variables have a significant impact on foreign exchange reserves. However, in the short term, the exchange rate has a positive and significant influence, while the policy rate has a negative and significant effect on Indonesia's foreign exchange reserves. A value speed of adjustment indicates that short-term imbalances are corrected towards long-term equilibrium each month, indicating a swift adjustment mechanism.